The Effect of Question Position on Listening Comprehension: A Case Study - Naci Yildiz; Nikoloz Parjanadze; Mustafa Albay (International Journal of Social Sciences & Educational Studies, 2015)
Though speaking has been considered as the most important skill in foreign language learning process, listening has a fundamental value because learning does not occur without comprehensible input. Listening is a complex process in which learners must do analysis to accurately interpret. In listening learners need to interpret with a speaker to construct meaning. This study tries to find out whether listening strategies are effective to influence listening comprehension and the major goal of the study is to reveal whether pre-listening, while- listening and post-listening activities are the most important to decipher the main idea of a listening text. It has been found that while-listening questions play the major role in comprehension of listening materials.